Three brown skuas at nest with chicks - Young, Euan (School of Biological Sciences, University of Auckland, 1992)
Most brown skua breed on the sub-Antarctic islands or the cold-temperate islands south of New Zealand. Some brown skua breed in communal groups consisting of three or more adult birds.